Expression of matrix metalloproteinase-2 in the extracellular matrix of osseointegrated and diseased implants - Ghada I Al-Duboni (College of Dentistry/ University of Baghdad, 2014)
Background: Recently with improvement of dental implantology science, osseointegrated implants show a considerable durability, however; failures are not completely avoidable. Matrix metalloproteinase-2 (MMP-2) expression is disturbed in many pathological conditions such as peri-implantitis and periodontitis. This study was carried out to investigate the tissue expression of MMP-2 in the extracellular matrix of osseointegrated and diseased implants. Subjects and methods: Gingival biopsies were collected from six patients having osseointegrated or working implants and twenty with diseased or non osseointegrated implants and (6) controls having no implants. In situ hybridization technique was used to analyze the changes in immunoreactivity of ECM-controlling MMP-2. Results: The findings of the present study indicate that the expression of MMP2 was significantly elevated in failed implants versus healthy implants (P